2. PREGNANCY OUTCOMES IN WOMEN WITH SEVERE PREECLAMPSIA AND ECLAMPSIA AT ADMISSION AT THE NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY: A CROSS-SECTIONAL STUDY (Tạp chí Y học Cộng đồng, 2025)
Objectives: To describe the characteristics and pregnancy outcomes of women diagnosed with severe preeclampsia and eclampsia who were admitted for emergency care at the National Hospital of Obstetrics and Gynecology.Subjects and methods: A cross-sectional descriptive study was conducted on 115 pregnant women diagnosed with severe preeclampsia or eclampsia who presented to the Emergency Department of the National Hospital of Obstetrics and Gynecology between June 2024 and March 2025.Results: The mean age of participants was 32.07 ± 6.9 years, with 38.3% aged 35 years or older. Clinical symptoms included edema (87.8%), blurred vision (14.8%), and headache (27%). At admission, 28.7% of women had stage 1 hypertension, 44.3% had stage 2 hypertension, and 25.2% had stage 3 hypertension. Severe preeclampsia accounted for 97.4% of cases, while 2.6% were diagnosed with eclampsia. HELLP syndrome was observed in 10.4% of patients, placental abruption in 0.9%, and 2.6% experienced other complications such as acute renal failure, pleural effusion, or coexisting Basedow’s disease. Regarding management, 99.1% of women underwent cesarean section, and 4.3% required referral to another facility. A total of 90.4% were treated with two or more antihypertensive medications, and 63.2% received intravenous magnesium sulfate (15%) for seizure prophylaxis. Following treatment and postpartum care, 95.7% of patients were discharged in stable condition. The mean gestational age at delivery was 33 ± 2.9 the mean neonatal birth weight was 1680 ± 680.4 grams. The live birth rate was 97.5%.Conclusion: Edema, headache, and blurred vision were the most common presenting symptoms among women with severe preeclampsia and eclampsia. The vast majority of cases were diagnosed as severe preeclampsia, and elective cesarean section was the predominant mode of delivery. Maternal outcomes were generally favorable, with most patients discharged in stable condition and a high fetal survival rate observed. These results underscore the importance of early recognition and timely management of preeclampsia and eclampsia to improve maternal and perinatal outcomes.
Keywords: severe pre-eclampsia; eclampsia.